Elektrik veriliş xətlərində cərəyan mühafizəsinin proqramlaşdırılan məntiqi kontrollerlər vasitəsilə modelləşdirilməsi - Əkbərov, Vüsаl; Bаbаyev, Cəmil; Qurbаnov, Elxаn; Rzаyev, Əli (My University, 2024)
It is known that the operating mode of the power system must be stable, reliable, uninterrupted, of high quality, and as economical as possible. The main elements ensuring the transmission and distribution of electric power to consumers are substations (EVX). Therefore, to maintain the mentioned operating conditions of the power system, the installation of relay protection and automation (RPA) in substations is provided.
Modeling of current protection in power transmission lines using programmable logic controllers
Keywords: Electrical networks; Electrical transmission lines